ANALYSIS AND INFLUENCE OF INDONESIAN FUN LEARNING AND CHARACTER EDUCATION LEARNING ACTIVITIES AT SDIU CAHAYA AL-FATIH SCHOOL, PANDEGLANG DISTRICT, BANTEN - Erwin, Erwin Hidayatullah; Yeni Sulaeman (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2024)
This research aims to investigate the Indonesian language learning process at SDIU Cahaya Al-Fatih Cangkuliang, Banten, as well as aspects that influence the quality of learning, including the role of teachers, teaching methods, learning resources, student responses, and the influence of parenting styles on student education and character. . Observations made show that the role of teachers in learning Indonesian is very important, with good interaction between teachers and students having a positive impact on learning motivation. However, obstacles such as students requiring additional time to absorb material require additional direction from the teacher. The use of varied and interactive teaching methods was identified as a key need to accommodate the different learning styles of students. Lack of access to supporting books in the learning process is an obstacle, resulting in the need to provide more diverse and supportive learning materials. Although the majority of students show good interest in learning Indonesian, further encouragement is needed so that all students can participate actively in the learning process. In addition, parenting styles at home are also identified as an important factor that influences students' education and character. The conclusions of this research emphasize the importance of a strong role of teachers, the use of varied learning methods, the availability of adequate learning resources, and collaboration with parents in forming supportive parenting patterns. Recommendations are given to improve the quality of Indonesian language learning at SDIU Cahaya Al-Fatih Cangkuliang.